Simulation of the Effect of Interference and EIRP on the Qos of DVB-S2 and DVB-RCS2 Networks - Heskia Jefri Saputra; M. Faiz Alfatih; Sabri Alimi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study was to obtain the QoS value of the data sent from the user terminal to the gateway based on variations in antenna gain and to determine the effect of the level of interference caused by noise on the user's device on the quality of data reception. This research uses the NS3 software experimental method. Parameters analyzed include throughput, delay, PDR. This study uses quasi-experimental methods. The purpose of quasi-experimental research is pure experimental conditions in conditions where it is impossible to control or manipulate all relevant variables, namely estimating. The conclusion in this study has been successfully carried out simulating sending data packets using the NS3 simulator tools. Based on the simulations that have been carried out, several characteristics of the effect of antenna gain on the quality of data packet transmission are obtained. The simulations explain well that the values of throughput, delay, and PDR have increased so as to provide good service quality. Based on the simulations that have been carried out, several characteristics of the influence of the interference level that affect the user on the quality of sending data packets are obtained. The simulation explains well that the values of throughput, delay, and PDR experience stability so that the level of interference has no effect on users in sending packets. However, the values obtained are very good and have not decreased